S-1 or gemcitabine adjuvant therapy in resected pancreatic cancer: a cost-effectiveness analysis based on the JASPAC-01 trial. (2nd January 2020) - Liao, Weiting; Huang, Jiaxing; Zhu, Guiqi; Zhou, Jing; Wen, Feng; Zhang, Pengfei; Zhou, Kexun; Wu, Qiuji; Wang, Xinyuan; Gou, Hongfeng; Li, Qiu
ABSTRACT: Purpose: This study aimed to investigate the cost-effectiveness of adjuvant treatments in resected pancreatic cancer. Methods: A Markov model was developed to mimic the disease process of postoperative pancreatic cancer, encompassing three health states (relapse-free survival, recurrent disease, and death). Health outcomes and utility scores were derived from the phase III trial and available literature. Cost data were calculated using standard fee data from the West China Hospital for 2017. One-way sensitivity analyses and probabilistic sensitivity analyses were developed to explore model uncertainty. Results: Treatment with S-1 was estimated to yield 1.61 quality-adjusted life-years (QALYs) at a cost of $25, 696, whereas treatment with gemcitabine yielded 1.27 QALYs at a cost of $28, 930. The incremental cost-effectiveness ratio of S-1 versus gemcitabine was $-9, 490 per QALY. Based on the willingness-to-pay threshold of $25, 841 per QALY, the net monetary benefit (NMB) was $15, 786 for S-1 and $3, 727 for gemcitabine, generating the incremental NMB of $12, 059. A probabilistic sensitivity analysis revealed that the probabilities of S-1 and gemcitabine being cost-effective were 92% and 8%, respectively. Results were robust to changes in parameters. Conclusion: Adjuvant therapy using S-1 is a cost-effective alternative compared to gemcitabine in patients with postoperative pancreatic cancer from the Chinese societal perspective.